Application of Liquid Chromatography/Tandem Mass Spectrometry for Quantitative Analysis of Plasmalogens in Preadolescent Children—The Hokkaido Study - Yifan Chen; Siddabasave Gowda B. Gowda; Divyavani Gowda; Jayashankar Jayaprakash; Lipsa Rani Nath; Atusko Ikeda; Yu Ait Bamai; Rahel Mesfin Ketema; Reiko Kishi; Hitoshi Chiba; Shu-Ping Hui (Diagnostics)
Background: Plasmalogens (Pls) are phospholipids with a unique structure, abundant in the brain and heart. Due to their chemical instability and analytical difficulties, less information is available compared to other phospholipids. The importance of Pls in several cellular processes is known, one of which is their protective effect against oxidative damage. The physiological role of Pls in human development has not been elucidated. Despite their clinical importance, the quantitative analysis of Pls in children’s plasma has been limited. Methods: This study aims to determine the plasma levels of Pls in prepubertal children using liquid chromatography/tandem mass spectrometry (LC-MS/MS). The plasma samples used were obtained from 9- to 12-year-old girls (n = 156) and boys (n = 178), n = 334 in total, who participated in the Hokkaido study. Results: Ethanolamine plasmalogen (PlsEtn) and choline plasmalogen (PlsCho), both carrying eicosapentaenoic acid, were significantly lower in girls than in boys. In both sexes, the plasmalogen levels for the 12-year-old children were lower than those for the 9-year-old children. PlsCho (16:0/18:2) was lower in the overweight children than in the normal-weight children for both sexes. PlsEtn (18:0/20:4) was the most abundant ethanolamine-type plasmalogen in both sexes. Conclusions: This study is the first report on plasmalogen levels and molecular types in children’s plasma. This study provides the information needed to understand the role of Pls in human developmental processes and may open up new opportunities in the future to control age-related changes in Pls.